I Patti Lateranensi visti da Luigi Salvatorelli una variante moderna (italiana e fascista) di un problema antico - Alciati, Roberto 1977- (2019)
In Luigi Salvatorelli the historian of Christianity is not separated from the political histo- rian. In an article of 1913 (“The history of Christianity and its relations with civil history”), Salvatorelli showed that in European historiography this relationship originated in Germany in the nineteenth century. However, German History of Christianity was characterized by a vice of an inimendable form: the theological presupposition. This led to an apologetic study of Christianity. The way out is to study Christianity not according to its alleged principle, but in constant relation with ‘civil’ or ‘profane’ history. Salvatorelli intends to investigate the interdependence between the ‘religious moment’ and the ‘profane moment’ that traditional historiography—both ‘theological’ and ‘civil’—could not grasp, having isolated and arbitrarily separated the two moments.
Keywords: Mussolini, Benito, 1883-1945; Catholic Church; Catholic Church ; Treaties, etc; Concordato fra la S Sede e l'Italia (1929 February 11); Fascism; Fascism and the Catholic Church; Lateran Treaty; Italian Catholic Church; state-church relations; reform of the church